Hypoxia-Induced Sarcoplasmic Reticulum Ca2+ Leak Is Reversed by Ryanodine Receptor Stabilizer JTV-519 in HL-1 Cardiomyocytes - Trinh, Minh Duc; Fiserova, Ivana; Vacek, Lukas; Marek, Marek; Pala, Jan; Tousek, Petr; Polak, Jan (Anatolian journal of cardiology, 2022)
BACKGROUND: To assess whether hypoxia, as can be found in obstructive sleep apnea syndrome, is causally associated with the development of heart failure through a direct effect on calcium leakage from the sarcoplasmic reticulum. METHODS: The impact of hypoxia on sarcoplasmic reticulum calcium leakage and expres- sion of RyR2 (ryanodine receptor2) and SERC2a (sarcoplasmic reticulum Ca2+ATPase 2a) was investigated together with the outcomes of JTV-519 and S107 treatment. HL-1 car- diomyocytes were cultured for 7 days on gas-permeable cultureware under control (12% O2) or hypoxic (1% O2) conditions with or without JTV-519 or S107. SRCL was assessed using a Fluo-5N probe. Gene and protein expression was analyzed using qPCR and western blotting. RESULTS: Hypoxic exposure increased sarcoplasmic reticulum calcium leakage by 39% and reduced RyR2 gene expression by 52%. No effect on RyR2 protein expression was observed. Treatment with 1μM JTV-519 reduced sarcoplasmic reticulum calcium leakage by 52% and 35% under control and hypoxic conditions, respectively. Administration of 1 μM JTV-519 increased RyR2 gene expression by 89% in control conditions. No effect on SRCL, RyR2, or SERC2a gene, or protein expression was observed with S107 treatment. CONCLUSION: Hypoxia increased sarcoplasmic reticulum calcium leakage which was ame- liorated by JTV-519 treatment independently of gene or protein expression. JTV-519 rep- resents a possible treatment for obstructive sleep apnea-associated HF.
Keywords: vápník; Myocytes, Cardiac; Ryanodine Receptor Calcium Release Channel; Hypoxia; Calcium; ryanodinový receptor vápníkového kanálu; kardiomyocyty; lidé; thiazepiny; Sarcoplasmic Reticulum; hypoxie; sarkoplazmatické retikulum; Humans; Thiazepines